1996
DOI: 10.1093/infdis/174.2.407
|View full text |Cite
|
Sign up to set email alerts
|

Direct Genetic Detection of Dobrav a Virus in Greek and Albanian Patients with Hemorrhagic Fever with Renal Syndrome

Abstract: Blood samples were collected from an Albanian and a Greek patient with hemorrhagic fever with renal syndrome and tested by reverse transcriptase-polymerase chain reaction. The genetic detection assay amplified hantavirus-specific DNA fragments from RNA extracted from the blood of the patients; nucleotide sequence analysis revealed that the causative agent of the disease was Dobrava virus. These findings suggest that Dobrava virus (which was originally isolated from the lungs of an Apodenws flavicollis mouse in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
53
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 14 publications
0
53
0
Order By: Relevance
“…A direct proof for DOBV-Af strains as an etiologic agent of HFRS was established by amplification of DOBV-Af nucleotide sequences from HFRS patients in Greece, Albania, and Croatia (1,25,33). HFRS cases caused by DOBV infection in South-East Europe were found to be clinically moderate or even severe with a case fatality index of up to 12% (1,3,22,33).…”
Section: Dobrava Virus (Dobv) Is a Hantavirus That Causes Hemorrhagicmentioning
confidence: 99%
See 1 more Smart Citation
“…A direct proof for DOBV-Af strains as an etiologic agent of HFRS was established by amplification of DOBV-Af nucleotide sequences from HFRS patients in Greece, Albania, and Croatia (1,25,33). HFRS cases caused by DOBV infection in South-East Europe were found to be clinically moderate or even severe with a case fatality index of up to 12% (1,3,22,33).…”
Section: Dobrava Virus (Dobv) Is a Hantavirus That Causes Hemorrhagicmentioning
confidence: 99%
“…A direct proof for DOBV-Af strains as an etiologic agent of HFRS was established by amplification of DOBV-Af nucleotide sequences from HFRS patients in Greece, Albania, and Croatia (1,25,33). HFRS cases caused by DOBV infection in South-East Europe were found to be clinically moderate or even severe with a case fatality index of up to 12% (1,3,22,33).In Central Europe, DOBV RNA has been predominantly detected in a different mouse species, the striped field mouse (A. agrarius). Phylogenetic analysis of these viral sequences from A. agrarius led to the definition of a second genetic DOBV clade, 50,51).…”
mentioning
confidence: 99%
“…2 An association of DOB virus with HFRS was recently found in patients from southeastern Europe (Albania, Greece, former Yugoslavia) and Russia. [5][6][7] In a study performed in Estonia (northeastern Europe), Plyusnin and others 8 demonstrated the presence of DOB virus in A. agrarius, the natural host of HTN virus in Asia. 1,2 In Slovakia (central Europe), HFRS is a well-known disease; clinical cases as well as infected rodents have been serologically diagnosed using HTN or PUU virus antigens.…”
mentioning
confidence: 98%
“…Puumala hantavirus (PUUV) causes a milder form of HFRS named nephropathia epidemica (NE), which occurs in northern and central Europe. The more severe forms of HFRS are caused by Hantaan (Asia) and Dobrava (Europe) viruses, while Seoul virus (worldwide) causes an intermediate form (3,17). Hantaviruses are carried by specific rodent hosts, and virus transmission to humans occurs via inhalation of aerosolized animal excreta (5, 32).…”
mentioning
confidence: 99%